ВЛИЯНИЕ ЛЕГИРОВАНИЯ НИКЕЛЕМ И МАРГАНЦЕМ НА КОНЦЕНТРАЦИЮ КИСЛОРОДА В КРЕМНИИ - Илиев, Х.М.; Турсунов, М.О.; Исамов, С.Б.; Ковешников, С.В. (SCIENCE and SOCIETY, 2022)
It was shown that the electrical properties of silicon containing binary nanocomplexes differ from the properties of conventional semiconductors, including silicon doped with various impurity atoms, with optical and electrical properties. It has been reported that nanocomplexes, which form silicon when manganese and nickel are introduced at high temperatures, affect optically active oxygen. The results obtained show that doping of manganese and nickel contributes to a decrease in the concentration of optically active oxygen.
Keywords: monocrystal; silicon; diffusion; nickel; manganese; Fure-spectrometer